DESIGNING A MOTORCYCLE SECURITY SYSTEM WITH INTERNET OF THINGS (IOT) AND BLUETOOTH TECHNOLOGY USING NODEMCU - Dody Wahjudi; Akhmad Fatkhi Rahmawan; Kholistianingsih Wahjudi; Isra’ Nuur Darmawan (Program Studi Teknik Elektro Universitas Peradaban, 2023)
The increase in motorcycle sales means that almost all people in the community can own a motorcycle, but if the development is not balanced with a security system, the theft rate becomes very high. Because in general, motorcycles use conventional locks that are easily damaged by thieves using a T lock. In this study, a motorcycle security system was created that combines Internet of Things technology with Bluetooth technology and is equipped with GPS (Global Positioning System).The microcontroller used is NodeMCU, the application of IoT and Bluetooth media and GPS is used for communication between the device and the Android Smartphone application. For its output using a relay module, the relay functions to turn on/off the contacts and motorcycle horn by giving commands through the application as a data sender. The GPS module will provide data on the coordinates of the motorcycle's location which is displayed on the GPS application of the tool.After testing the entire system, both applications and a series of components have different responses. IoT media has a response that depends on the internet connection used. the response of turning on the contact is 0.89 seconds and the horn is 0.89 seconds, turning off the contact is 0.84 seconds and the horn is 1.05 seconds. The bluetooth media response is turning on the contact which is 0.94 and the horn is 0.42 seconds, turning off the contact is 0.69 seconds and the horn is 1.10 seconds. In the GPS system, the difference in distance between the GPS device and the GPS smartphone is 2.67 meters.